OPT: optimal human visual system-aware and power-saving color transformation for mobile AMOLED displays - Jin, Jeong Chan; Lee, Jae Hyeok; Kim, Eun Sil; Kim, Young Jin (Multimedia Tools and Applications, 2018)
Organic light-emitting diode (OLED) displays have a high power efficiency; however, the frequent use of user interaction-based applications such as instant messengers, video players, and games contributes strongly to the total power consumption. The power consumption varies significantly depending on the display contents, and thus, color transformation, which is a representative low-power technique, is used for OLED displays. Previously developed low-power color transformation methods have not been thoroughly researched for satisfying the human visual system and have not considered optimal visual satisfaction and power consumption simultaneously. In this paper, a novel low-power color transformation approach is proposed, which is aimed at simultaneously optimizing both visual satisfaction and power consumption. In addition, it is implemented on an active-matrix OLED (AMOLED) display-based Android smartphone at runtime. Experimental results show that the proposed technique achieves better human visual satisfaction and shows up to 22.32% power saving on average on the AMOLED display and offers 6.23% more extended battery life over that of an existing leading technique.
Keywords: AM-OLED; Color transformation; Human Visual System; Image quality assessment; Power savings; Color transformation; Human visual system; Image quality assessment; Mobile AMOLED display; Power saving